Latest avenues on solar light-driven photocatalytic hydrogen generation using surface modified nanomaterials towards sustainable environment and circular bioeconomy. (15th May 2023) - Sathish, S.; Aravind kumar, J.; Prabu, D.; Annam Renita, A.; Murugesan, Karthikeyan; Rajasimman, M.; Joo, Sang-Woo; Vasseghian, Yasser; Wang, Chongqing
Graphical abstract: Highlight: Various photocatalysts were examined to convert solar energy into clean H2 fuel. Water splitting with a photocatalyst under irradiation was reviewed. The doping co-catalysts and comparing different photocatalysts were discussed. Hydrogen production was improved with photocatalyst's surface and composition modifications. Abstract: The developing interest in energy has started to work to our advantage in growing clean and electrified energy sources to supplant oil-based commodities.The global use of petroleum derivatives is increasing at an alarming and unsustainable rate, resulting in environmental damage such as releasing toxic contaminants and greenhouse gases. Nanomaterials constantly changing in their configuration may be required to a transition to a green energy-based economy. The photocatalytic water splitting method holds promise for producing hydrogen quickly and effectively. Solar energy can split water to create hydrogen, making it a valuable renewable energy source. Either co-catalysts or dopants have been added to the current photocatalysts for improvement. In this article, novel nanophotocatalysts for rational hydrogen synthesis and modified photocatalysts are discussed. The results can highlight the synthesis of nanostructured materials that demonstrate favorable catalytic properties, which can be achieved as alternative and stable catalysts for efficient hydrogen production withoutmuch environmental adverse impacts.